Further insight into the roles of the chemical composition of dissolved organic matter (DOM) on ultrafiltration membranes as revealed by multiple advanced DOM characterization tools. (June 2018) - Ly, Quang Viet; Hur, Jin
Abstract: This study assessed the relative contributions of different constitutes in dissolved organic matter (DOM) with two different sources (i.e., urban river and effluent) to membrane fouling on three types of ultrafiltration (UF) membranes via excitation emission matrix - parallel factor analysis (EEM-PARAFAC), size exclusion chromatography (SEC), and Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). Two polyethersulfone membranes with different pore sizes and one regenerated cellulose membrane were used as representative hydrophobic (HPO) and hydrophilic (HPI) UF membranes, respectively. Although size exclusion effect was found to be the most prevailing rejection mechanism, the behaviors of individual fluorescent components (one tryptophan-like, one microbial-humic-like, and terrestrial humic-like) and different size fractions upon the UF filtration revealed that chemical interactions (e.g., hydrophobic interactions and hydrogen bonding) between DOM and membrane might play important roles in UF membrane fouling, especially for small sized DOM molecules. Based on the molecular level composition determined by FT-ICR-MS, the CHOS formula group showed a greater removal tendency toward the HPO membrane, while the CHONS group was prone to be removed by the HPI membrane. The changes in the overall molecular composition of DOM upon UF filtration were highly dependent on the sources of DOM. The molecules of more acidic nature tended to remain in the permeate of effluent DOM, while the river DOM was shifted into more nitrogen-enriched composition after filtration. Regardless of the DOM sources, the HPO membrane with a smaller pore size led to the most pronounced changes in the molecular composition of DOM. Graphical abstract: Image 1 Highlights: Size exclusion was found to be a prevailing fouling mechanism for urban river DOM. Chemical interactions potentially operate between small sized DOM molecules and UF membranes. CHOS and CHONS formulas showed greater removals on HPO and HPI membranes, respectively. FT-ICR-MS shows superior ability in tracking DOM molecular composition upon UF.